Optimalisasi Kompetensi Guru Matematika SMA di Mojokerto dalam Menyusun Soal AKM Numerasi: Optimizing the Competence of High School Mathematics Teachers in Mojokerto to Preparing AKM Numeration - Kuswandari, Inna; Wahyuni, Yayuk; Winarko, Edi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Assessments in learning are important to obtain information about students' achievements toward expected competencies, including cognitive and non-cognitive learning outcomes. Cognitive learning outcomes are measured through the Minimum Competency Assessment (AKM) which measures reading literacy and mathematics/numeracy literacy abilities. This requires teachers to always improve their competence in learning, especially in providing AKM questions as a tool to help students understand learning. The Mathematics Study Program, Faculty of Science and Technology, Airlangga University, through community service activities in collaboration with the high school mathematics teacher’s group in Mojokerto and SMA Negeri 1 Puri Mojokerto, held activities to improve teacher competence in providing AKM questions. The series of activities started with training in preparing AKM numeracy, assignments to participants accompanied by mentoring, providing participant feedback, as well as evaluating the entire activity. From these activities, it can be concluded that this training activity is very useful and has been proven to increase teacher competence in compiling AKM questions independently. The results of feedback from training participants showed positive responses from participants to the training material and the capabilities of speakers and instructors. Therefore, similar activities that lead to increasing teacher competency must be one of the priority programs for stakeholders, including schools and local governments.